2020
DOI: 10.1371/journal.pone.0235741
|View full text |Cite
|
Sign up to set email alerts
|

Changes in infant non-nutritive sucking throughout a suck sample at 3-months of age

Abstract: The goal of this study was to compare how infants' non-nutritive suck (NNS) changes throughout a suck sample. Fifty-four full-term infants (57% male) completed this study at, on average, 3.03 (SD .31) months of age. These infants sucked on our custom research pacifier for approximately five minutes. Infants produced, on average, 14.50 suck bursts during the sample. NNS data was pooled across subjects and breakpoint analyses were completed to determine if there were changes in their NNS patterning. Breakpoints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…While relatively little data are available on NNS, especially for infants residing in Puerto Rico, NNS metrics in our study participants are largely consistent with prior literature reported on infants 0–3 months ( Zimmerman and Foran, 2017 ; Zimmerman et al, 2020 ). For example, in a study of 26 full-term infants, Martens et al (2020) reported comparable ranges of NNS, with mean NNS frequency of 2.09 Hz (versus 1.9 ± 0.2 Hz in our study), mean cycles per burst of 9.6 (versus 11.5 ± 6.5 in our study), and average amplitude of 14.05 cmH 2 O (versus 17.1 ± 6.9 cmH 2 O in our study).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While relatively little data are available on NNS, especially for infants residing in Puerto Rico, NNS metrics in our study participants are largely consistent with prior literature reported on infants 0–3 months ( Zimmerman and Foran, 2017 ; Zimmerman et al, 2020 ). For example, in a study of 26 full-term infants, Martens et al (2020) reported comparable ranges of NNS, with mean NNS frequency of 2.09 Hz (versus 1.9 ± 0.2 Hz in our study), mean cycles per burst of 9.6 (versus 11.5 ± 6.5 in our study), and average amplitude of 14.05 cmH 2 O (versus 17.1 ± 6.9 cmH 2 O in our study).…”
Section: Discussionsupporting
confidence: 89%
“…Two minute periods of sucking were analyzed to quantify several measures of NNS, including cycle count, amplitude (cmH 2 0), burst duration (s), frequency (Hz), bursts/min, cycles/min, and cycles/burst. A burst was defined as the group of cycles between two pauses taken by the infant for respiration ( Zimmerman et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data were pooled across participants and breakpoint analyses were used to see if there were certain points throughout the sample where the NNS patterning changed. Breakpoints were found for the amplitude, or strength, of the suck and the amount of suck cycles per burst, but frequency remained stable throughout the sample(35). This aligns with prior findings ofCapilouto et al and Zimmerman et al where NNS frequency was consistent across studies, 2.02 HZ, 2.16 HZ and 2.11 Hz respectively…”
supporting
confidence: 88%
“…We hypothesized that amplitude, cycles/burst, duration, number of cycles, and number of bursts would be significantly different between the 3-and 12month timepoints, and that NNS frequency would remain relatively stable between the two timepoints. This hypothesis is based on data showing NNS frequency to be relatively stable with a NNS sample (35) and in response to sensory stimulation (8,9). We anticipated that aspects of NNS would change based on maturation and feeding experiences over the first year of life.…”
Section: Changes In Non-nutritive Suck Between 3 and 12 Monthsmentioning
confidence: 99%